Carlyle the tragedian: staging Euripides' Bacchae in The French Revolution. (12th July 2018) - Mebane, Julia
Abstract: The Victorian historian Thomas Carlyle wrote The French Revolution, the work that established his literary fame, in sustained dialogue with classical antiquity. Yet while his engagement with Homeric epic is often noted, his indebtedness to Greek tragedy is rarely acknowledged. This article argues that Carlyle staged 'The Insurrection of Women', his account of the women's march on Versailles in October 1789, as a figurative production of Euripides' Bacchae. Identifying the marchers as Maenads, adopting the voice of the chorus, and invoking themes of sacrifice and regicide, Carlyle represents historical events in tragic terms. He thereby circumvents what he sees as the 'linearity' of narrative to recreate the 'solidity' of history. The text that results is paradigmatic of his philosophy of history, which insists upon irrationality as inherent to humanity. Positing sacrificial violence as the seed from which civilization begins and to which it must return, Carlyle presents Greek tragedy as one lens through which revolution becomes legible.